Synergistic interactions between imatinib mesylate and the novel phosphoinositide-dependent kinase-1 inhibitor OSU-03012 in overcoming imatinib mesylate resistance - Tseng, Ping-Hui (© 2005 by The American Society of Hematology, 2005)
Resistance to the Ableson protein tyrosine (Abl) kinase inhibitor imatinib mesylate has become a critical issue for patients in advanced phases of chronic myelogenous leukemia. Imatinib-resistant tumor cells develop, in part, as a result of point mutations within the Abl kinase domain. As protein kinase B (Akt) plays a pivotal role in Abl oncogene-mediated cell survival, we hypothesize that concurrent inhibition of Akt will sensitize resistant cells to the residual apoptotic activity of imatinib mesylate, thereby overcoming the resistance. Here, we examined the effect of OSU-03012, a celecoxib-derived phosphoinositide-dependent kinase-1 (PDK-1) inhibitor, on imatinib mesylate-induced apoptosis in 2 clinically relevant breakpoint cluster region (Bcr)-Abl mutant cell lines, Ba/F3p210(E255K) and Ba/F3p210(T315I). The 50% inhibitory concentration (IC(50)) values of imatinib mesylate to inhibit the proliferation of Ba/F3p210(E255K) and Ba/F3p210(T315I) were 14 ± 4 and 30 ± 2 μM, respectively. There was no cross-resistance to OSU-03012 in these mutant cells with an IC(50) of 5 μM irrespective of mutations. Nevertheless, in the presence of OSU-03012 the susceptibility of these mutant cells to imatinib-induced apoptosis was significantly enhanced. This synergistic action was, at least in part, mediated through the concerted effect on phospho-Akt. Together these data provide a novel therapeutic strategy to overcome imatinib mesylate resistance, especially with the Abl mutant T315I.